Efektivitas Strategi Pembelajaran Berbasis Masalah Dalam Meningkatkan Kemampuan Berfikir Siswa - Nur Aliyah Alfita; Dedi Harianto; Nur Aliyah Alfita; Nadhila Ramadhani; Abd. Wahid; Muhammad Alfie Sukri; Muh. Fadhil Fahlan (Contemporary Education Review, 2025)
Problem-Based Learning (PBL) is an effective approach for enhancing students' critical thinking skills by promoting active engagement through collaboration and real-world problem-solving. This study employs a literature review method to analyze previous research on PBL, focusing on data collection from secondary sources such as academic journals and research reports. The findings indicate that PBL significantly improves students' critical thinking abilities, despite challenges in implementation, such as time constraints and teacher preparedness. The PBL process involves several stages, including problem orientation, fact gathering, authentic investigation, action planning, and evaluation. This approach not only enhances critical thinking but also prepares students to face real-life challenges, fostering resilience and adaptability